A short review on transparent and colorless polyimides - Ha, Chang-Sik (Vietnam Journal of Science and Technology, 2022)
. Polyimides are known as high performance polymers that are widely used in opto-electronic devices as well as other high engineering applications. Among polyimides, in particular transparent and colorless polyimides (CPIs) are recently in high demand in opto-electronic industries because of their transparency as well as balanced thermo-mechanical properties. It is known that the charge transfer complex (CTC) formation in aromatic polyimides provides them to have brownish-yellow colors as well as optical opaqueness, for which their application in optoelectronic devices are limited, while the CTC also donates a high glass transition temperature (Tg) by restricting their segmental mobility. In this short review, recent trends to prepare CPIs with balanced thermo-mechanical properties were overviewed, which have been reported mainly by our group for years, with expecting to be a useful guideline to the synthesis and design of CPIs. Main efforts to synthesize CPIs have been generally oriented toward to the reduction of the intra- or inter charge transfer interactions between diamines and dianydrides in the aromatic polyimides through the design conceptions including the incorporation of bulky substituents, non-coplanar segments, fluorine atoms, and alicyclic diamines and dianhydrides, etc. to prepare PIs. Thus prepared CPIs possess good transparency and colorlessness with high Tg’s.